Nucleation and growth of polycrystalline SiC - Kaiser, Michl; Schimmel, Saskia; Jokubavicius, Valdas; Linnarsson, Margareta K.; Ou, Hayan; Syväjärvi, Mikael; Wellmann, Peter (IOP Conference Series: Materials Science and Engineering, 2014)
The nucleation and bulk growth of polycrystalline SiC in a 2 inch PVT setup using isostatic and pyrolytic graphite as substrates was studied. Textured nucleation occurs under near-thermal equilibrium conditions at the initial growth stage with hexagonal platelet shaped crystallites of 4H, 6H and 15R polytypes. It is found that pyrolytic graphite results in enhanced texturing of the nucleating gas species. Reducing the pressure leads to growth of the crystallites until a closed polycrystalline SiC layer containing voids with a rough surface is developed. Bulk growth was conducted at 35 mbar Ar pressure at 2250 degrees C in diffusion limited mass transport regime generating a convex shaped growth form of the solid-gas interface leading to lateral expansion of virtually [001] oriented crystallites. Growth at 2350 degrees C led to the stabilization of 6H polytypic grains. The micropipe density in the bulk strongly depends on the substrate use
Keywords: fluorescent SiC; PVT; nucleation; polycristalline growth